The world economy between the world wars - Feinstein, C. H.; Temin, Peter; Toniolo, Gianni, 1942- (Oxford : Oxford University Press, 2008)
Expanded from a previous volume dealing with Europe, new material in this book focuses on the structure of the world economy in the 1920s, including a special focus on the United States, Japan, and Latin America. In addition, chapters that discuss the post-depression recovery now cover the New Deal.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Economic history -- 1918-1945.